ANALYSIS OF STUDENTS' NUMERICAL ABILITY IN THE PROCESS OF FINANCIAL ACCOUNTING LECTURES (AN EXPERIMENT ON ECONOMICS EDUCATION STUDY PROGRAM, FKIP UNTAN) - Warneri Warneri (Sean Institute, 2023)
The purpose of this study was to determine students' numerical abilities in accounting lectures through the lecture implementation process and student final test results in introductory accounting courses, intermediate financial accounting, intermediate finance 1, intermediate financial accounting 2 and advanced financial accounting. Numerical ability is a basic ability that students must haveFkip Untan Economics Education Study Program. Researchers stated the need for repairs and improvements by lecturers regarding financial accounting lectures, so that students have numerical skills when carrying out the learning process at school or in non-educational fields and maximize the lecture process and students of economics education study programs still experience difficulties in completing calculations of accounting questions. This research method uses a descriptive qualitative method through experiments on students of the Economics Education Study Program, FKIP Untan. The research sample included all regular economics study program students. The data collection tools are (a) tests (numerical ability questions) and (b) observation guidelines (financial accounting learning outcomes).